The Talent Show Activity Book - Ladybird Readers Level 3 - Morris,Catrin (Ladybird, 2017)
The A-Stars played music and the Zigzags danced. They both wanted to win the Harmony School Talent Show! Ladybird Readers is a graded reading series of traditional tales, popular characters, modern stories, and non-fiction, written for young learners of English as a foreign or second language. Beautifully illustrated and carefully written, the series combines the best of Ladybird content with the structured language progression that will help children develop their reading, writing, speaking, listening and critical thinking skills. The five levels of Readers and Activity Books follow the CEFR framework and include language activities that provide preparation for the Cambridge English: Young Learners (YLE) Starters, Movers and Flyers exams.